Engineering vibration analysis with application to control systems - Beards, C. F. (Edward Arnold, 1995)
Most machines and structures are required to operate with low levels of vibration as smooth running leads to reduced stresses, fatigue, and noise. This book explains the principles and methods used to analyze the vibration of engineering systems and describes how these techniques and results can be applied to the study of control system dynamics.
Keywords: Vibration.; Automatic control.; elektronické knihy; electronic books